2004
DOI: 10.1080/1540496x.2004.11052566
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Inflation in Emerging Markets by Using the Phillips Curve and Alternative Time Series Models

Abstract: The aim of this paper is to investigate the performance of the Phillips curve to forecast inflation in a high inflation emerging market country by taking Turkey as a case. For this purpose, we compare the forecasting performance of the Phillips curve with alternative time series models, namely, the univariate ARIMA model, vector autoregression and vector error correction model, and a naive no-change model. The data pertains to the quarterly inflation rate in Turkey for the 1987-2001 period. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…There is a growing consensus that theoretical models are more accurate in forecasting when the economy is weak, especially during periods of economic crises, compared with ARIMA, Naïve and VAR models (Buelens, 2012;Dotsey, Fujita, & Stark, 2011;Onder, 2004). For example, Onder (2004) used quarterly data between 1987: q1 and 1999: q4 to forecast Turkish inflation with the Phillips curve, ARIMA, Vector Autoregression (VAR), VECM and naive models. The evidence revealed that the Phillips curve model outperformed other models for one-quarter ahead forecasts and the prediction of the 2001 financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing consensus that theoretical models are more accurate in forecasting when the economy is weak, especially during periods of economic crises, compared with ARIMA, Naïve and VAR models (Buelens, 2012;Dotsey, Fujita, & Stark, 2011;Onder, 2004). For example, Onder (2004) used quarterly data between 1987: q1 and 1999: q4 to forecast Turkish inflation with the Phillips curve, ARIMA, Vector Autoregression (VAR), VECM and naive models. The evidence revealed that the Phillips curve model outperformed other models for one-quarter ahead forecasts and the prediction of the 2001 financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few studies also found Multivariate VAR model produce a better forecast than alternative models over the long horizon (Canova, 2007;Onder, 2004;Fritzer, Moser, & Scharler, 2002;Fanchon & Wendel, 1992). For example, Gupta, Eyden, and Waal (2015) examine whether the global vector autoregressive (GVAR) approach forecasts better than a vector error correction model (VECM) and a BVAR model for two key South African variables, GDP output and inflation between the period 1979q2-2009q4.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, there is some debate on whether the Phillips Curve trade-off exists in Turkey (e.g. Kuştepeli, 2005;Onder, 2004Onder, , 2009. We hypothesize that this debate may reflect the difficulty in establishing a Phillips Curve if strong distributional effects from relative price changes are omitted from the model.…”
Section: Introductionmentioning
confidence: 95%
“…The literature on the Phillips Curve relates inflation to output or unemployment gaps (e.g. Onder, 2004Onder, , 2009Kuştepeli, 2005;de Mendonça, 2009). The literature on relative price variability relates inflation to the second and third moments of relative price changes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five years after Phillips's paper, Robert Lucas and Thomas Sargent set the simultaneously high inflation and unemploymentevident across practically all developed economies -against a Phillips curve backdrop and decried the econometric failure on a grand scale. This followed a sequence of papers during the 1970s that had both supported and called into question the econometric and theoretical basis of the Phillips curve and hence its usefulness for public policy purposes (Lipsey, 1960;Solow, 1970;Onder, 2004 andFaridul et al, 2011).…”
Section: Introductionmentioning
confidence: 99%